2010
DOI: 10.1111/j.1399-6576.2010.02243.x
|View full text |Cite
|
Sign up to set email alerts
|

Fusion of dispatching centres into one entity: effects on performance

Abstract: The reform increased the total number of ambulance dispatches, prolonged answering and call processing times and had a negative effect on the appropriate use of ambulances. The accuracy of risk assessment was not affected. Evidence-based data should be the basis for the future as dispatching centre processes are shown to be vulnerable during organisational reforms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 18 publications
1
7
0
3
Order By: Relevance
“…This result is in concordance with a previous study which showed that a well-trained and functioning EMCC is able to detect high-risk patients who require highest-priority [7]. However Määttä and colleagues conclude that the EMCC organization reform in Finland did not affect the accuracy of assessing potentially life-threatening conditions [5]. The varying results between our studies may be caused by the fact that different variables were used to evaluate the organization changes.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This result is in concordance with a previous study which showed that a well-trained and functioning EMCC is able to detect high-risk patients who require highest-priority [7]. However Määttä and colleagues conclude that the EMCC organization reform in Finland did not affect the accuracy of assessing potentially life-threatening conditions [5]. The varying results between our studies may be caused by the fact that different variables were used to evaluate the organization changes.…”
Section: Discussionsupporting
confidence: 91%
“…The public media and local EMS organizations discussed whether the new EMCC organization was worse for the patient and they argued that there was a risk that patients would not get an ambulance when needed. A recently published study by Määttä and colleagues describes that the EMCC organization reform in Finland had negative effects on the appropriate use of ambulances, and the reform caused prolongation in the answering and processing times of emergency calls in Helsinki, the capital of Finland [5]. …”
Section: Introductionmentioning
confidence: 99%
“…In 2006, Finland implemented a nationwide standardization of the EMCCs. However, it has been previously reported that this change did not improve the accuracy of risk assessment as evaluated by correct recognition of cardiac arrest, stroke, and STEMI patients in one of the regional dispatch centres [17]. This fact further highlights the need for focused studies to re-evaluate the current protocol.…”
Section: Discussionmentioning
confidence: 97%
“…Police dispatching centre was integrated into emergency medical and fire dispatching centre in October 2005. 9 Helsinki EMS is three tiered, and the services for urgent calls are provided by the fire department. The first tier consists of 7-9 basic life support (BLS) ambulances (depending on the time of the day) manned by EMTs.…”
Section: Emsmentioning
confidence: 99%
“…The median (interquartile range) times for all 120 operations were time from request to dispatching 120 sec (66-240), time from dispatching to the arrival of the first unit on the scene 10 min (7)(8)(9)(10)(11)(12)(13)(14), time from dispatching to the arrival of the medical supervisor unit on the scene 15 min (11-17) and duration of the…”
Section: Time Intervalsmentioning
confidence: 99%